Diversity of growth performance and rumen microbiota vary with feed types - Du, Shuai; Bu, Zhenkun; You, Sihan; Bao, Jian; Jia, Yushan (Frontiers in Sustainable Food Systems, 2022)
Diet is a major factor in influencing the growth performance and the microbial community of lambs. The present study aimed to investigate animal performance and rumen microbiota influenced by diverse diets. Ninety male lambs were randomly assigned into three groups with a completely randomized design with equal lambs: non-pelleted native grass hay (HA) as the control diet, pelleted native grass hay (GP), and pelleted native grass hay with concentrate (GPC) diets. The rumen fluid samples of the lambs in the HA, GP and GPC groups were used to study rumen microbiota diversity through 16S rDNA high throughput sequencing. Compared to the HA group, the higher final body weight, dry matter intake and average daily gain were found in the GP and GPC groups, similarly, the better animal performance was observed in the GPC group. The principal coordinates analysis displayed that the composition of the rumen microbiota in the three groups was distinctly separated from each other. Generally, Bacteroidetes and Firmicutes were the dominant members of the community in the HA and GP groups, while Bacteroidetes, Firmicutes and Proteobacteria became the predominant members in the GPC group. The comparison among these groups showed significant (p < 0.05) differences in Rikenellaceae_RC9_gut_group, Prevotella_1, Ruminococcaceae_NK4A214_group and Succiniclasticum. These results suggest that the GP and GPC diets are more beneficial for growth performance than the HA diet, and also indicate that the rumen microbiota varied in response to different feed types. In conclusion, these results could provide strategies to influence rumen microbiota for better animal performance and healthier in the Mongolian Plateau ecosystem, and lay a theoretical basis for feeding the native grass diet.